ATTITUDES OF WOMEN IN THE REPUBLIC OF MACEDONIA FOR PRENATAL TESTING AS A PREVENTIVE PUBLIC HEALTH PROCEDURE (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2014)
Prenatal screening and diagnostic tests are associated with great anticipation, many questions, and different attitudes for the condition of the fetus, as well as providing important information about the health and condition of the future baby. The study included 507 respondents. The aim of the research is to determine the attitudes of Macedonian women for prenatal testing as preventive public health procedures, depending on their demographic characteristics. The research is an analytical sectional study whose results were collected by a questionnaire that was made for the purposes of the study, and included women-mothers with at least one pregnancy. To follow the observation about attitudes toward prenatal screening and diagnostic procedures, a descriptive analysis of the total number of points was made, where we found that surveyed women in Macedonia don`t have precisely built views ( opinions ) regarding prenatal screening and diagnostic procedures . The higher level of attitudes towards prenatal screening and diagnostic procedures associated with respondents of age group under 49 years, who are residing in the city, with high educational level, married, nationality Macedonians, have health insurance, those who have children with developmental disabilities and women with one to two pregnancies. But although there are differences in demographic characteristics, respondents in 67.1 % are unanimous in terms of attitude that prenatal screening tests should be used by all pregnant women. For this view is unspecified are 25.2%, 7.7 % of the respondents disagree .